2021
DOI: 10.1016/j.rpsm.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of lifestyle changes during the COVID-19 pandemic using a multidimensional scale

Abstract: Introduction Healthy lifestyles are relevant to several diseases and to maintain individuals’ mental health. Exposure to epidemics and confinement have been consistently associated with psychological consequences, but changes on lifestyle behaviours remain under-researched. Materials and Methods An online survey was conducted among the general population living in Spain during the COVID-19 home-isolation. In addition to demographic and clinical data, participants self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 39 publications
9
123
0
3
Order By: Relevance
“…The findings hint to a complex picture with some positive and negative effects of home confinement. Physical activity and changes in sleeping patterns have been reported also in the adult population [178] , [179] , [180] , [181] , [186] . A sample of more than participants in the UK provides some hints about the magnitude of physical activity variation before and during the lockdown [179] .…”
Section: Surveysmentioning
confidence: 86%
“…The findings hint to a complex picture with some positive and negative effects of home confinement. Physical activity and changes in sleeping patterns have been reported also in the adult population [178] , [179] , [180] , [181] , [186] . A sample of more than participants in the UK provides some hints about the magnitude of physical activity variation before and during the lockdown [179] .…”
Section: Surveysmentioning
confidence: 86%
“…Lifestyle habits were assessed using the Short Multidimensional Inventory Lifestyle Evaluation–Confinement (SMILE-C) [ 41 ]. This scale was developed specifically to allow a multidimensional measure of lifestyle during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, consistent results point to the beneficial effects of physical activity in preventing the onset of depression as well as improving its symptoms [ 40 ]. As many people around the world are under confinement due to the COVID-19 pandemic, changes in lifestyle behaviors have attracted more research interest [ 41 ]. Behaviors, such as sleep quality [ 36 , 42 ], were assessed among HCWs instead of using a comprehensive, multidimensional approach to lifestyle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worse sleep quality with confinement has been reported among the adult general population in different countries (11)(12)(13)65), and partly attributed to inactivity (12) and higher anxiety and mental distress during isolation (21). In our study, the association with mental health during quarantine was confirmed, with an increased risk of reducing sleep quality in individuals with higher GDS-10 scores (RRR: 1.25; 95%CI: 1.13-1.39; data not shown in tables).…”
Section: What Do Other Studies Say About Changes In Sleep Duration Anmentioning
confidence: 99%